GROUNDWATER FLOW CHARACTERIZATION IN THE VICINITY OF THE UNDERGROUND CAVERNS IN FRACTURED ROCK MASSES BY NUMERICAL MODELING - Yang H.S.; Kang J.G.; Kim K.S.; Kim C.S. (My University, 2004)
Groundwater inflow into the caverns constructed in fractured bedrock was simulated by numerical modeling: NAP-SAC (DFN, discrete fracture network model) and NAMMU (CPM, continuous porous media model), which is a finite-element software package for groundwater flow in 3D fractured media developed by AEA Technology, UK. The input parameters for modeling are based on surface fracture survey, core logging and single hole hydraulic test data. In order to predict the groundwater inflow as accurately as possible, the anisotropic hydraulic conductivity was considered. The anisotropic hydraulic conductivities were calculated from the fracture network properties and the in-situ fracture data. With a minor adjustment during model calibration, the numerical modeling is able to reasonably reproduce groundwater inflows into the cavern as well as the travel lengths and the surface arrival times through the flow paths.
Keywords: 3D fractured media; anisotropic hydraulic conductivitiy; DFN model; CPM model; roundwater inflows